Diagnosing Organizational Change: How The Implications To Employee And Organization Performances - Prita Ayu Kusumawardhany (Conference In Business, Accounting, And Management (CBAM), 2012)
Business environment with continual changing and tight competition required each organization to survive and win the competition. Organizations are required to learn and to grow in gaining competitive advantage. Organization’s ability to survive is determined by the ability of organizations to change, adapt to changing business environment and potential changes that could occur in the future. This study describes the process of change that happened on one of a state owned company in Indonesia with 17 (seventeen) diagnosed key elements of the changes model by using the Readiness for Change by Stewart. From the diagnosed process, it could be seen the changes had been taken place so far and the reaction or response from the organization players, which can be useful in searching for factors that can support and hinder the implementation of change within an organization and how much GAP happened. The better reaction from the players would give the organization positive implications on employee performance and also the performance of the organization. The type of research is using explanatory. This research used a case study, using interviews, observation and screening the company’s internal documents to obtain necessary data.Keywords:      organization change, readiness for change model, 17 (seventeen) key elements, employee performances, organization performance